1998
DOI: 10.4153/cjm-1998-043-x
|View full text |Cite
|
Sign up to set email alerts
|

Tableaux Realization of Generalized Verma Modules

Abstract: ABSTRACT. We construct the tableaux realization of generalized Verma modules over the Lie algebra sl(3Ò C). By the same procedure we construct and investigate the structure of a new family of generalized Verma modules over sl(nÒ C).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 8 publications
0
13
0
1
Order By: Relevance
“…This theory was generalized to orthogonal Lie algebras in [Ma3] and to quantum algebras in [MT]. It was also very useful for the study of various categories of U n -modules, see [Kh,Ma1,Ma4 A major step in the development of the theory of Gelfand-Zeitlin modules was made in [Ov1,Ov2] (it was also put into a more general setup in [FO], see also [FMO, FOS]) where it was, in particular, shown that all Gelfand-Zeitlin characters 1 The surname Zeitlin appears in the literature in different spellings, that is in different latinizations of the Cyrillic version of the original Latin (German) surname, in particular, it was spelled as Cetlin, Zetlin, Tzetlin and Tsetlin. Here we use the original Latin spelling.…”
Section: Introduction and Description Of The Resultsmentioning
confidence: 99%
“…This theory was generalized to orthogonal Lie algebras in [Ma3] and to quantum algebras in [MT]. It was also very useful for the study of various categories of U n -modules, see [Kh,Ma1,Ma4 A major step in the development of the theory of Gelfand-Zeitlin modules was made in [Ov1,Ov2] (it was also put into a more general setup in [FO], see also [FMO, FOS]) where it was, in particular, shown that all Gelfand-Zeitlin characters 1 The surname Zeitlin appears in the literature in different spellings, that is in different latinizations of the Cyrillic version of the original Latin (German) surname, in particular, it was spelled as Cetlin, Zetlin, Tzetlin and Tsetlin. Here we use the original Latin spelling.…”
Section: Introduction and Description Of The Resultsmentioning
confidence: 99%
“…One of the main advantages of Gelfand-Zetlin modules is that many Gelfand-Zetlin modules admit a so-called tableau realization, that is an explicit combinatorial construction in which a basis of the module is indexed by a set of tableaux (defined by imposing some conditions on the entries) and the action of the generators e i,i+1 and e i+1,i of g is given by the so-called Gelfand-Zetlin formulae, see [DFO], [Maz1], [Maz2] for details. In such a realization the tableaux represents a basis of common eigenvectors for Γ (as mentioned above, the corresponding eigenvalues are computed as certain symmetric functions), and the action of e i,i+1 (resp.…”
Section: Gelfand-zetlin Realizationmentioning
confidence: 99%
“…It is related to many concepts arizing in Mathematics and Physics, see for example [1,2,4,9,[15][16][17]19,20]. The general theory of Gelfand-Tsetlin modules for gl n was developed in [3,[5][6][7]10,22,23,25,26], and references therein. For U q (gl n ) certain families of Gelfand-Tsetlin modules were constructed in [12,24], while the general theory was developed in [8].…”
Section: Introductionmentioning
confidence: 99%